Dutch disease in former Soviet Union: Witch-hunting? - Balázs Égert (Center for Social and Economic Research (CASE), 2009)
This study seeks to determine the extent to which countries of the former Soviet Union are infected” by the Dutch Disease. We take a detailed look at the functioning of the transmission mechanism of the Dutch Disease, i.e. the chains that run from commodity prices to real output in manufacturing. We complement this with two econometric exercises. First, we estimate nominal and real exchange rate models to see whether commodity prices are correlated with the exchange rate. Second, we run growth equations to analyse the possible effects of commodity prices and the dependency of economic growth on natural resources.
Keywords: E31; F31; O11; P17; 330; Dutch disease; exchange rate; growth; oil; commodity prices; CIS; transition; Rohstoffreichtum; Wechselkurs; Rohstoffpreis; GUS-Staaten